2020
DOI: 10.1109/access.2020.2973037
|View full text |Cite
|
Sign up to set email alerts
|

An Enriched Time-Series Forecasting Framework for Long-Short Portfolio Strategy

Abstract: Stock return forecasting typically requires a large number of factors and these factors usually exhibit nonlinear relations with each other. Conventional methods of stock return forecasting mainly fall into two categories: Technical Analysis and Fundamental Analysis. Technical Analysis focuses on time-series data, while Fundamental Analysis explores low-frequency fundamental variables. Although there are substantial works on either time-series analysis or fundamental analysis, few studies have enriched the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Traditionally, price analysis is divided into fundamental and technical analysis [11]. Te stock price can be afected by news, events, and information about the release of new products.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, price analysis is divided into fundamental and technical analysis [11]. Te stock price can be afected by news, events, and information about the release of new products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since we previously said that we avoid the strategy of holding stocks for a long time, our algorithm will be based on making a proft during one trading day. Although studies [11,15,19] indicate that good profts can be expected during the month, the indicators of a good fnancial report set the general trend in the dynamics of the company's stock price chart. However, we still want to maximize the annual income of the portfolio by increasing trading operations with a small amount of invested money.…”
Section: Price Prediction Experiments For Building Trading Strategymentioning
confidence: 99%
“…The existence of certain financial derivative instruments enable the monetization of the forecasted TTE map by our proposed models. Typical examples include future contracts, which enable the construction of a long-short investment portfolio [25], [84], [85]. With proper position sizing [86] and risk management, the signals or forecast derived from the model can be transformed into an investment strategy.…”
Section: A Impacts Of Concordance Indexmentioning
confidence: 99%
“…The third type of work (Classification), classifies indicator data from a stock as "Buy", "Hold", or "Sell" through deep learning and neural network based classifications [31], [32], [33], [34], [16]. Prediction results can also represent an "Up" or "Down" trend so that investors can make decisions on investment entry positions by applying two single non-linear classifiers ANN, SVM and one RF ensemble approach to predict the direction of the next day's movement [35], [5], [36].…”
Section: Using a Clustering Algorithm Shares Will Be Grouped Against An Investment Decision Making Criterion (Clustering)mentioning
confidence: 99%
“…For example, [10] used indicator technical data to predict stocks on the China Shanghai Stock Exchange market, then [11] proposed stock predictions using a combination of types of technical and macroeconomic indicator data sets. combining technical indicators and news sentiment through text mining techniques such as [12], [13], [14], [4], [15], research [16], [3], [17] also found that the company's fundamentals had a positive impact on changes in the company's stock price.…”
Section: Introductionmentioning
confidence: 99%